Assessment of Patient Safety Culture in an Adult Oncology Department in Saudi Arabia - Alharbi, Waleed (Oman Med J, 2018)
OBJECTIVES: We sought to evaluate patient safety culture across different healthcare professionals from different countries of origin working in an adult oncology department in a medical facility in Saudi Arabia. METHODS: This cross-sectional survey of 130 healthcare staff (doctors, pharmacists, nurses) was conducted in February 2017. We used the Hospital Survey of Patient Safety Culture (HSOPSC) to examine healthcare staff perceptions of safety culture. RESULTS: A total of 127 questionnaires were returned, yielding a response rate of 97.7%. Eight out of 12 HSOPSC composites were considered areas for improvement (percent positivity < 50.0%). Significantly different mean scores were observed across the three professional groups in all 12 HSOPSC composites. Doctors tended to rate patient safety culture significantly more positively than nurses or pharmacists. Nurses scored significantly lower than pharmacists in the majority of HSOPSC composites. No significant differences in patient safety culture composite scores were observed between Saudi/Gulf Cooperation Council (GCC) and non-Saudi/GCC groups. Regression analysis showed that the frequency of reported events is predicted by feedback and communication about errors, and teamwork across units. Perception of patient safety is associated with respondents’ profession and teamwork across units. CONCLUSIONS: This study brings to the fore the assumption that all healthcare professionals have a shared understanding of patient safety. We urge healthcare leaders and policy makers to look at patient safety culture at this granular level in their contexts and use this information to develop strategies and training to improve patient safety culture.